Why So Many Local Entrepreneurs? - Michelacci, Claudio; Silva, Olmo (The Review of Economics and Statistics, 2007)
We document that the fraction of entrepreneurs working in the region where they were born is significantly higher than the corresponding fraction for dependent workers. This is more pronounced in more developed regions and positively related to the degree of local financial development. Firms created by locals are bigger, operate with more capital-intensive technologies, and obtain greater financing per unit of capital invested, than firms created by nonlocals. This suggests that there are so many local entrepreneurs because locals can better exploit the financial opportunities available in the region where they were born. This helps to explain how local financial development causes persistent disparities in entrepreneurial activity, technology, and income.